Norms and institutional obstacles cause differences in women's and men's adoption of climate-smart agriculture - Muneri, Eunice Wangari (CGIAR GENDER Impact Platform, 2023)
Deep-rooted social-cultural norms and institutional obstacles contribute to different levels of climate-smart agriculture adoption between women and men farmers. Multipronged approaches that bundle technical and social interventions are needed to address the obstacles. Addressing these obstacles can improve the gender-equitable uptake of climate-smart agriculture practices.